(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The article describes the main issues of formation and optimization of the system of financial management of enterprise based on the analysis of investments in its marketing activities. Analyzed theoretical approaches to the financial management of the business and its interdependence with investment analysis and marketing activities of enterprises. Investigated basic indicators of efficiency of investments into marketing activities of the company. Developed scheme of optimization of system of financial management based on the analysis of investments in its marketing activities, consisting of three levels of indicators, namely: financial management, analysis of investments in marketing activities and other indicators. Revealed advantages and disadvantages of this optimization scheme.